2022
DOI: 10.1038/s41598-022-07409-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants on lipid oxidation in herring (Clupea harengus) co-product silage during its production, heat-treatment and storage

Abstract: Provided high product quality, ensilaging can be used to valorize fish filleting co-products into a silage suitable for food applications. However, a documented challenge for products from hemoglobin-rich fish raw materials is the high susceptibility to lipid oxidation, calling for stabilization by antioxidants. In a comparison among different rosemary-containing antioxidants and isoascorbic acid, we here found that the commercial mixture Duralox MANC-213 (MANC) provided the best protection against peroxide va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
1
13
1
1
Order By: Relevance
“…Contrary, a high TBARS value was recorded in the herring co-product even before ensilaging, which after 1 h decreased significantly ( p < 0.05) and remained constant at ~ 8–9 µmole TBARS/kg silage thereafter. Overall, the TBARS values recorded in this study were slightly lower than in our previously reported lab-scale ensilaging of herring co-products at 21–22 °C with 0.25–1.25% BORDANTIX W/S or BORDANTIX O/S antioxidant added; 8–9 µmole and 20–28 µmole TBARS/kg silage, respectively (Sajib et al, 2022 ). The lower TBARS values recorded in this study could possibly be due to the use of higher quality starting raw material as ensilaging was done on-site at the herring processing plant within 1–2 h after the generation of co-products.…”
Section: Resultscontrasting
confidence: 78%
See 4 more Smart Citations
“…Contrary, a high TBARS value was recorded in the herring co-product even before ensilaging, which after 1 h decreased significantly ( p < 0.05) and remained constant at ~ 8–9 µmole TBARS/kg silage thereafter. Overall, the TBARS values recorded in this study were slightly lower than in our previously reported lab-scale ensilaging of herring co-products at 21–22 °C with 0.25–1.25% BORDANTIX W/S or BORDANTIX O/S antioxidant added; 8–9 µmole and 20–28 µmole TBARS/kg silage, respectively (Sajib et al, 2022 ). The lower TBARS values recorded in this study could possibly be due to the use of higher quality starting raw material as ensilaging was done on-site at the herring processing plant within 1–2 h after the generation of co-products.…”
Section: Resultscontrasting
confidence: 78%
“…Lab-scale ensilaging of herring filleting co-products has previously been reported, e.g., by our team (Sajib et al, 2020 , 2022 ), but also by, e.g., van’ t Land et al ( 2017 ). Briefly, ensilaging can be performed by adding 2.5% v/w formic acid (85% purity) to minced herring co-products to lower the pH below 4.0, and the protein degree of hydrolysis (DH) can then be tuned by terminating the autolysis after a specific time.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations